Performance on a domain-general and a domain-specific cognitive task during exercise: what are the effects of exercise intensity, exercise modality, and time of cognitive assessment among highly-trained athletes? - Dong, L.; Romeas, T.; Vincent, T.; Bherer, L.; Berryman, N. (International Journal of Sport and Exercise Psychology, 2026)
This study examined cognitive performance during exercise and the effects of exercise intensity, exercise modality, cognitive task type, and time of assessment, as well as assessed the accompanying self-reported measures. Eighteen highly-trained and elite water polo players (21.04 ± 3.27 years of age; 12 male, 6 female) completed a dual-task protocol on two occasions: once performing a domain-general task (Stroop test with three cognitive trial types) and once performing a domain-specific task (water polo video-based test) during cycling exercise. The exercise involved three work-matched bouts of cycling: continuous moderate intensity, continuous high intensity, and interval high intensity. Self-reported measures (rating of perceived exertion, affect, mental effort, mental and physical demands) were recorded after each exercise condition. There were exercise intensity-related effects on Stroop performance only, including faster reaction time during moderate-intensity exercise for naming trials (p < 0.001), and interactions with cognitive trial type (p = 0.037). There were no differences between continuous and interval high-intensity exercise conditions for either performance or self-reported responses. Notably, mental effort and demand, in addition to physical effort and demand, were perceived to be significantly higher for the Stroop task than for the video-based test despite identical exercise conditions. Furthermore, Stroop accuracy was associated with more positive affect (r = 0.47) and lower ratings of physical demand (r = -0.37). These findings imply possible task-specificity of athletes` dual-task performance. They also support the importance of further exploring how task duration and participants' perceptions relate to executive function performance during exercise.